Evidence for Reversal of Immunosuppression by Homeopathic Medicine to a Predominant Th1-type Immune Response in BALB/c Mice Infected with Leishmania donovani - Joshi, Jyoti; Bandral, Chetna; Manchanda, Raj Kumar; Khurana, Anil; Nayak, Debadatta; Kaur, Sukhbir (Homeopathy, 2021)
Background Visceral leishmaniasis (VL) is a neglected tropical disease that is fatal if treatment is not given. The available chemotherapeutic options are unsatisfactory, and so complementary therapies like homeopathy might be a promising approach.Methods A nosode from a pure axenic culture of Leishmania donovani was prepared and screened for its anti-leishmanial potential both in an in-vitro and an in-vivo experimental approach.Results Leishmania donovani amastigote promastigote nosode (LdAPN 30C) exhibited significant anti-leishmanial activity against the promastigote forms of Leishmania donovani and was found to be safe. A study conducted on VL-infected mice revealed that LdAPN 30C resolved the disease by modulating the host immune response toward the Th1 type through upregulating the pro-inflammatory cytokines (IFN-γ and IL-17) and inducing nitric oxide (NO) levels in the infected macrophages. The hepatic parasite load was also found to be significantly decreased. The nosode was found to be safe, as no histological alterations in the liver or kidney were observed in the animals treated with the LdAPN 30C.Conclusion This is the first study in which an axenic culture of Leishmania donovani has been used for the preparation of a homeopathic medication. The study highlights the anti-leishmanial and immunomodulatory potential of a homeopathic nosode in experimental VL.
Keywords: visceral leishmaniasis; homeopathy; cytokines; nitric oxide; immune response